2018
DOI: 10.1016/j.uclim.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the local and global implications of air pollution trends in Zaria, northern Nigeria

Abstract: Highlights• Pioneer outdoor air pollution time-series data for a Nigerian city • Validates MSA Altair 5× gas detector and CW-HAT200 particulate counter.• Alarming outdoor pollution measurements • A candidate into the list of World's most polluted cities is revealed. AbstractAir pollution is an unnoticed problem in many Nigerian urban cities. This is mainly attributed to the usage of power generating sets, indiscriminate refuse burning, biomass consumption and import/recycle of timeworn automobiles, which domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 23 publications
1
24
1
Order By: Relevance
“…This result indicates a significant concern [ 51 , 52 ] observing ambient particulate matter pollution had a sharp shoot of associated deaths in 2012 ( Figure 4 d) and DALYs in 2015 ( Figure 5 c), both with minimal changes till 2017. Ambient air pollution is a top risk factor responsible for reducing longevity in global GBD ranking [ 20 , 53 ], likewise in Nigeria. Studies showed an increase in the outdoor air pollution level in Nigeria, mainly from anthropogenic sources in the urban cities, summing up to more exposure to the population in such urban areas [ 53 , 54 ].…”
Section: Health Effects Of Environmental Risk Factors In Nigeriamentioning
confidence: 99%
See 1 more Smart Citation
“…This result indicates a significant concern [ 51 , 52 ] observing ambient particulate matter pollution had a sharp shoot of associated deaths in 2012 ( Figure 4 d) and DALYs in 2015 ( Figure 5 c), both with minimal changes till 2017. Ambient air pollution is a top risk factor responsible for reducing longevity in global GBD ranking [ 20 , 53 ], likewise in Nigeria. Studies showed an increase in the outdoor air pollution level in Nigeria, mainly from anthropogenic sources in the urban cities, summing up to more exposure to the population in such urban areas [ 53 , 54 ].…”
Section: Health Effects Of Environmental Risk Factors In Nigeriamentioning
confidence: 99%
“…Ambient air pollution is a top risk factor responsible for reducing longevity in global GBD ranking [ 20 , 53 ], likewise in Nigeria. Studies showed an increase in the outdoor air pollution level in Nigeria, mainly from anthropogenic sources in the urban cities, summing up to more exposure to the population in such urban areas [ 53 , 54 ]. Global average life expectancy is between 60-70years; however, in Nigeria, it is reported to be 54.4yers according to WHO [ 55 ].…”
Section: Health Effects Of Environmental Risk Factors In Nigeriamentioning
confidence: 99%
“…Although often studied as a separate phenomenon, especially when it comes to its health effects, indoor air-polluting activities also contribute a great deal to the overall urban ambient air quality [ID3]. This effect is strongest in lower-income neighborhoods of ECOWAS cities, such as Accra (Ghana), where indoor cooking from wood or coal and heating activities that produce emissions are a common feature of domestic life [46,47]…”
Section: Polluting Sourcesmentioning
confidence: 99%
“…Regarding Nigeria, Aliyu and Botai [47] state that the monitoring network is "scantily distributed", which implies there are stations, but their location or functionality is not mentioned. Another study [17] shows a figure where two Federal Ministry of the Environment sampling sites are located, in the Rivers State cities of Peter Odili and Abuloma, near Port Harcourt.…”
Section: Monitoriong Stations and Data Availabilitymentioning
confidence: 99%
See 1 more Smart Citation